Fire hazard trajectories under climate change and management scenarios: Research note - Rodrigues Mimbrero, Marcos (Geographicalia, 2023)
Research note on the FirePATHS Project - "Fire hazard trajectories under climate change and management scenarios" led by Marcos Rodrigues and funded by the Spanish Ministry of Science and Innovation (PID2020-116556RA-I00). The project aims to evaluate the evolution of fire danger under different emission concentration and forest management scenarios through the explicit interaction of the climate-vegetation-fire system. The core of the process lies in the modelling of vegetation dynamics at stand scale under different climate evolution trajectories, in order to characterise the state and typology of fuels, and the subsequent simulation of potential fire behaviour (e.g. rate of spread or intensity of burning). It is a novel strategy for assessing possible trajectories of evolution in the current context of global change, providing a vision especially focused on developing a framework for forest management aimed at mitigating fire risk. In this sense, the methodology allows assessing, among others, the potential for burning intensity, crown fire probability, derived emissions or the duration of the fire season. The ultimate goal of the project is to provide and evaluate effective forest management strategies for fire risk mitigation based on the main narratives and lines of intervention in the European context (promotion of biomass use, ecosystem services or fuel management through prescribed burning).